On the Aesthetic Paradigm and Perception of Music (Journal of Global Arts Studies, 2023)
Background: Music is a sensory art based on sound, and its aesthetic paradigm is established on the reasonable combination and arrangement of sounds. Purpose: This article analyzes human perception of sound from an aesthetic perspective, attempting to explain the factors that influence whether music is perceived as "pleasant" or "unpleasant." Methods: The essential attribute of music is the effect of perceived sound on the object, which means that subjects with different perceptual abilities will have varying aesthetic experiences based on different aesthetic paradigms. Simultaneously, different aesthetic paradigms will also affect one's feelings towards music. This explains why different ages, regions, and ethnicities have various aesthetic differences in music. Results: This paper aims to analyze the connection between paradigms and perception through the internal mechanisms of aesthetic paradigms and attempts to explain the causes leading to different aesthetic tastes, contributing to the spread and creation of music by exploring human consciousness level understanding of sound. Conclusion: The results show that music aesthetics and human perception are strongly linked and explain to some extent the elements that influence humans' subjective judgments of music.
Keywords: Aesthetic Paradigm; Music Aesthetics; Perception; Sound Cognition